Autophosphorylation of p110delta phosphoinositide 3-kinase: a new paradigm for the regulation of lipid kinases in vitro and in vivo - Vanhaesebroeck, B; Higashi, K; Raven, C; Welham, M; Anderson, S; Brennan, P; Ward, S G; Waterfield, M D (The EMBO journal, 1999)
Phosphoinositide 3-kinases (PI3Ks) are lipid kinases which also possess an in vitro protein kinase activity towards themselves or their adaptor proteins. The physiological relevance of these phosphorylations is unclear at present. Here, the protein kinase activity of the tyrosine kinase-linked PI3K, p110delta, is characterized and its functional impact assessed. In vitro autophosphorylation of p110delta completely down-regulates its lipid kinase activity. The single site of autophosphorylation was mapped to Ser1039 at the C-terminus of p110delta. Antisera specific for phospho-Ser1039 revealed a very low level of phosphorylation of this residue in cell lines. However, p110delta that is recruited to activated receptors (such as CD28 in T cells) shows a time-dependent increase in Ser1039 phosphorylation and a concomitant decrease in associated lipid kinase activity. Treatment of cells with okadaic acid, an inhibitor of Ser/Thr phosphatases, also dramatically increases the level of Ser1039-phosphorylated p110delta. LY294002 and wortmannin blocked these in vivo increases in Ser1039 phosphorylation, consistent with the notion that PI3Ks, and possibly p110delta itself, are involved in the in vivo phosphorylation of p110delta. In summary, we show that PI3Ks are subject to regulatory phosphorylations in vivo similar to those identified under in vitro conditions, identifying a new level of control of these signalling molecules.